(untitled) (Indian Journal of Veterinary Pathology, 2026)
Enterotoxaemia remains one of the most economically important Clostridial diseases of small ruminants, which often occurs in peracute form with sudden mortality without any premonitory signs. Thus, the present study was undertaken to determine the occurrence of enterotoxaemia in sheep and goat flocks with the history of sudden death in Namakkal and Karur regions of Tamil Nadu. Totally, 62 flocks with the history of sudden death were investigated and samples like intestinal contents in necropsied animals and faecal swabs from live animals were collected. Among these, 22 flocks were found positive for different toxinotypes of Clostridium perfringens by multiplex PCR, which include 14 sheep flocks and 8 goat flocks. The study revealed that the major etiological agent for sudden death in small ruminants was C. perfringens type D and highest occurrence was recorded in sheep. Similarly, male lambs and kids were more susceptible than females. With respect to age, lambs and kids in the age group of 4 to 6 months were mostly affected. The findings also revealed, enterotoxaemia is more prevalent in the extensive system of management. Among the different toxinotypes, Type D is most commonly observed in both dead and live animals, followed by Type A. Thus, the present study highlights the continued endemicity of enterotoxaemia in this region and stresses the need for periodical vaccination, proper dietary management, disease surveillance and regular monitoring for effective disease control.